BLENDING: SEBUAH ALTERNATIF DALAM PENAMAAN MAKANAN DAN MINUMAN RINGAN - Giyatmi, Giyatmi; Wijayava, Ratih; Arumi, Sihindun (Sunan Kalijaga State Islamic University Yogyakarta, 2018)
This research aims at finding kinds of blend and describing the formation of blend in snack names found in supermarket around Sukoharjo, Central Java. This research is a descriptive qualitative research. Data of this research are the blend which are used in snack brands. The data are taken from several shops and supermarkets such as Indomaret, Alfamart, Mitra, Jumbo, and Hyperrmart in Sukoharjo area. This research uses observation and writing techniques. The data analysis consists of data reduction, data display, and data verification. The data reduction is done by reducing snack brands with no blend in the data collection process. The research uses triangulation theory to deal with the types of blend and the formation of blend. The research finds 62 data of snack brands which use blend. There are three kinds of blend, such as blend with clipping (51 data), blend with phonemic overlapping (7 data), and blend with overlapping and clipping (4 data). Most of the blends are blends with clipping because they are the easiest way to create a new word using blend. Meanwhile, there are 13 ways of blend formation.